Reputasi Badan Gizi Nasional dalam Menangani Pemberitaan Negatif di Media Digital Terkait Pengelolaan Program Makan Bergizi Gratis (MBG) - Marsha Amina Safira; Najwa Shahab; Karimah Faizah; Nasywa Rahmadhita; Tria Patrianti (CV. ITTC INDONESIA, 2026)
The National Nutrition Agency (BGN) is an Indonesian government agency dedicated to fulfilling the nutritional needs of the Indonesian people. Established in 2024, the new agency has a vision and mission to build a healthier Indonesian nation. They began their journey by launching their first program, Free Nutritious Meals (MBG). MBG is a BGN program aimed at improving the nutritional status of the Indonesian people. However, throughout the MBG program, there has been much public debate. From food poisoning issues to MBG cars hitting students, the program has raised public concerns. Furthermore, the management of the MBG program has also been questioned by the public, from the categorization of community groups deemed inappropriate to the issue of the Head of BGN, Dadan Handayana, who is suspected of being involved in a corruption case. All of the problems that have befallen BGN due to the ongoing MBG program have questioned its success in the public eye. Through online news, the public has provided negative comments about the MBG program, which has impacted BGN's reputation as an institution that promotes the MBG program. Therefore, the purpose of this study is to analyze and observe the National Nutrition Agency's actions in addressing negative news coverage in digital media related to MBG management. This research approach uses qualitative methods, with data collection techniques including digital media observation, literature review, and media monitoring.